Agreement between questionnaires and registry data on routes to diagnosis and milestone dates of the cancer diagnostic pathway. (April 2020) - Falborg, Alina Zalounina; Vedsted, Peter; Menon, Usha; Weller, David; Neal, Richard D.; Reguilon, Irene; Harrison, Samantha; Jensen, Henry; ,
Highlights: We found reasonable agreement on routes to diagnosis and milestone dates in the cancer pathway between patient, physicians and cancer registry. Agreement on routes to diagnosis was higher for breast cancer than for colorectal, ovarian and lung cancers. Agreement on date of diagnosis date was higher than for date of first presentation to primary care and date of treatment. Combining multiple data sources can provide more complete and reliable information on the cancer diagnostic pathway. Abstract: Background: The routes to diagnosis and the time intervals along the diagnostic pathway affect cancer outcomes. Some data on routes to diagnosis and milestone dates can be extracted from registries or databases. When this data is incomplete, inaccurate or non-existing, other data sources are needed. This study investigates the agreement between multiple data sources on routes to diagnosis and milestone dates of cancer pathway. Methods: Information on routes to diagnosis and milestone dates were compared across four data sources (cancer patients, general practitioners, cancer specialists and registries) for breast, colorectal, lung and ovarian cancers across the UK, Scandinavia, Canada and Australia. Agreement on routes to diagnosis and milestone dates was assessed by Kappa and AC1 coefficients and Lin's concordance correlation coefficient (CCC). Results: 4502 patients were included in the analysis of routes to diagnosis. The agreement was almost perfect (kappa = 0.15–0.88, AC1 = 0.86–0.91) for breast cancer, substantial to almost perfect (kappa = 0.07–0.86, AC1 = 0.74–0.93) for colorectal and ovarian cancers, and substantial (kappa = 0.09–0.11, AC1 = 0.65–0.74) for lung cancer. 2287 patients were included in the analysis of milestone dates. The agreement was adequate for all cancer types (CCC = 0.88–0.99); highest agreement was seen for date of diagnosis (CCC = 0.94–0.99). Conclusion: We found a reasonable agreement between patient/physician questionnaires and registry data for routes to diagnosis and milestone dates. The agreement on routes to diagnosis was generally higher for breast cancer than for colorectal, ovarian and lung cancers. Lower agreement was seen on date of first presentation to primary care and date of treatment initiation compared to date of diagnosis.